Usages et mésusages de la durabilité forte. Introduction au dossier « Regards disciplinaires et perspectives critiques sur la durabilité forte en SHS » - Caroline Lejeune; Clémence Guimont (Développement Durable et Territoires)
This paper introduces the Special section entitled “Disciplinary Perspectives and Critical aspects on Strong Sustainability in Social Sciences and Humanities". It asks about the theoretical significance of the notion of strong sustainability in the fields of economics, philosophy and political science. This introduction aims at presenting the theoretical debates on this notion and to draw a brief overview of its anchoring and influence in social sciences and humanities. It highlights some of the strengths and limits of this notion, since the accentuation and acceleration of global environmental disturbances, question the capacity of social sciences and humanities to study the economic, social and political consequences of the finiteness of nature. Scientific works mobilizing strong sustainability have also focused on solutions to get out of this situation.